2021
DOI: 10.3390/ijms22158208
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Approaches for Alzheimer’s Disease: An Updated Review

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease and accounts for most cases of dementia. The prevalence of AD has increased in the current rapidly aging society and contributes to a heavy burden on families and society. Despite the profound impact of AD, current treatments are unable to achieve satisfactory therapeutic effects or stop the progression of the disease. Finding novel treatments for AD has become urgent. In this paper, we reviewed novel therapeutic approaches in five categories:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 246 publications
(256 reference statements)
0
44
0
1
Order By: Relevance
“…A comprehensive discussion of amyloid-directed AD therapeutics is beyond the scope of this paper; however, recent reviews have provided thorough coverage of this topic ( Bullain and Doody, 2020 ; Avgerinos et al, 2021 ; Decourt et al, 2021 ; Jeremic et al, 2021 ; Lin et al, 2021 ; Restifo, 2021 ; Sun et al, 2021 ; Van Bokhoven et al, 2021 ; Xie et al, 2021 ; Yu et al, 2021 ). Jeremic et al (2021) summarized the late-stage clinical failures of eight secretase inhibitors, and they report on the clinical status of eight amyloid-directed monoclonal antibodies.…”
Section: The Current Status Of Amyloid-targeting Experimental Therape...mentioning
confidence: 99%
“…A comprehensive discussion of amyloid-directed AD therapeutics is beyond the scope of this paper; however, recent reviews have provided thorough coverage of this topic ( Bullain and Doody, 2020 ; Avgerinos et al, 2021 ; Decourt et al, 2021 ; Jeremic et al, 2021 ; Lin et al, 2021 ; Restifo, 2021 ; Sun et al, 2021 ; Van Bokhoven et al, 2021 ; Xie et al, 2021 ; Yu et al, 2021 ). Jeremic et al (2021) summarized the late-stage clinical failures of eight secretase inhibitors, and they report on the clinical status of eight amyloid-directed monoclonal antibodies.…”
Section: The Current Status Of Amyloid-targeting Experimental Therape...mentioning
confidence: 99%
“…Although in animal studies Epothilone D rescued working and spatial memory deficits in aged tau transgenic mice (reviewed in Yu et al, 2021), this drug was discontinued following a Phase 1 clinical study in 2013, with no information regarding drug's effectiveness and side effects in humans (Bristol-Myers Squibb, 2013). 2.…”
Section: Microtubule Stabilizersmentioning
confidence: 99%
“…The clinical trials performed in humans with tauopathies had no positive outcome (Ivashko-Pachima and Gozes, 2021). In a phase II double-blind randomized controlled trial, NAP showed cognitive and functional improvement in mild cognitive impairment (MCI) patients, after a 12-week intranasal NAP administration (reviewed by Yu et al (2021). By the time this review is being written, clinical trials on MCI, progressive supranuclear palsy and schizophrenia have all been discontinued, and the one for frontotemporal dementia is inactive (as per alzforum webpage 20.09.2021).…”
Section: Microtubule Stabilizersmentioning
confidence: 99%
“…In recent years, clinical trials of several drugs targeting Aβ, such as BACE1 inhibitors and anti-Aβ monocolonal antibodies, have failed, implicating the importance of targeting pathologies other than Aβ. Thus, more attention has been paid to drug candidates acting on other targets, including tau and neuroinflammation [ 10 ]. However, the Aβ oligomer hypothesis is still considered to be valid, and AβOs are attractive targets for the development of therapeutic candidates.…”
Section: Introductionmentioning
confidence: 99%